Mechanism for Determining New Students Based Online at MIN 3 Banda Aceh - Arifa, Munada Nuril; Tihalimah, Tihalimah (Al-Fikrah, 2025)
Digital transformation in Indonesia's education sector, particularly the implementation of an online new student registration system, has significantly impacted efficiency and accessibility. This research focuses on MIN 3 Banda Aceh, which faces challenges related to infrastructure and technological understanding amid social diversity. A descriptive qualitative method was used to explore the experiences of administrators, parents, and prospective students through interviews and observations. The results indicate an increase in participation and parental trust in data security, although challenges still need to be addressed. These findings delve into the importance of integrating local values and Islamic education management principles in creating an inclusive and transparent system, with the hope of providing recommendations for better educational management in the future.